Exact Solutions in Classical Field Theory: Solitons, Black Holes and Boson Stars - Boulanger, Nicolas; Campoleoni, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Special Issue in honour of Prof. Yves Brihaye, on the occasion of his 65th birthday. The issue is mainly dedicated to the study of compact objects and solutions to Einstein-Yang-Mills equations and extensions thereof, topics to which Prof. Y. Brihaye contributed very significantly.